Influence of a liquid surface on the NOx production of a cold atmospheric pressure plasma jet. (10th September 2018) - Hansen, Luka; Schmidt-Bleker, Ansgar; Bansemer, Robert; Kersten, Holger; Weltmann, Klaus-Dieter; Reuter, Stephan
Abstract: In this work a cold atmospheric pressure plasma jet was mounted above a distilled water reservoir to study the influence of a water surface on reactive oxygen and nitrogen species (RONS) generation. The RONS, namely O3 and NO2, were measured by multi-pass cell Fourier transform infrared absorption spectroscopy in the far-field of the jet. A shielding gas device was used to control the ambient environment of the effluent. The liquid surface has nearly no influence on the RONS dynamics as a function of shielding gas composition. It was found, however, that the interaction with the liquid surface increases the density of NO x by a factor of 2–3 due to local increase in H2 O concentration through evaporation of water from the liquid surface. In contrast to the case of ambient humidity increase, this locally higher H2 O density distinctly influences the ratio of water to oxygen and nitrogen which results in a higher generation of OH molecules.